Diversifying philosophy of religion: critiques, methods and case studies - Loewen, Nathan R. B.; Rostalska, Agnieszka (Expanding philosophy of religion, 2023)
"Much philosophical thinking about religion in the Anglophone world has been hampered by the constraints of Eurocentrism, colonialism and orientalism. Addressing such limitations head-on, this exciting collection develops models for exploring global diversity in order to bring philosophical studies of religion into the globalized 21st century. Drawing on a wide range of critical theories and methodologies, and incorporating ethnographic, feminist, computational, New Animist and cognitive science approaches, an international team of contributors outline the methods and aims of global philosophy of religion. From considering the importance of orality in African worldviews to interacting with Native American perspectives on the cosmos and investigating contemplative studies in Hinduism, each chapter demonstrates how expertise in different methods can be applied to various geographical regions, building constructive options for philosophical reflections on religion. Diversifying Philosophy of Religion raises important questions regarding who speaks for and represents religious traditions, setting the agenda for a truly inclusive philosophy of religion that facilitates multiple standpoints"--